The effect of residual stress on the nonsingular T-stresses - A.S. Chernyatin; Yu.G. Matvienko; I.A. Razumovsky (Fracture and Structural Integrity)
The effect of residual stresses on surface fatigue crack propagation and fracture mechanics parameters of intersecting orthogonal cracks is discussed. Mutual influence of intersecting cracks and biaxiality affects the nonsingular parameters Txx and Tzz. At the same time, the effect on the stress intensity factor is negligible. Two-parameter fracture mechanics is employed for an analysis of fatigue crack propagation taking into account residual stresses. The final configuration of the crack front is close to the semi-elliptical configuration.